Proximate composition, fatty acids and cholesterol content of meat cuts from tegu lizard Tupinambis merianae - Caldironi, Hugo Alfredo (2006)
The proximate composition, fatty acid composition and cholesterol content of three different cuts of meat from tegu Tupinambis merianae were determined. Moisture (72.0±0.7%), protein (23.6±0.7%), fat (4.0±1.3%) and ash (1.2±0.2%) did not differ from values obtained from beef or chicken meat. The cholesterol content (18.2±5.8 mg/100 g tissue) was similar among the cuts and was lower in tegu meat than in other meats of similar fat content such as beef, chicken or fish. The relation between polyunsaturated and saturated fatty acids (1.09) was comparable to that of some species of fish, and the fat presents nutritional qualities comparable with those of chicken meat.